Схема сперматогенеза у гирокотилид - Базитов, А.А.; Ляпкало, Э.В. (Вестник зоологии, 1982)
The mode of spermatogenesis in Gyrocotyle sp. is described. During two meiotic divisions the cell number in cytophores increases in a sequence of 16, 32, 64.. S u c h a t y p e of spermatogenesis is common t e r c o m e r e except for caryophilids whose
cytophores contain, as a rule, a nigner number or cells.